FORMAÇÃO E ATUAÇÃO DAS PROFESSORAS INDÍGENAS DA ALDEIA PIAÇAGÜERA - Alves, Oneide Ferraz (2007)
This project investigate the indian teachers preparation and behavior of Escola Estadual Indígena Tupi-Guarani Ywy Pyaú, that is in Peruíbe, in South Coast of São Paulo. It s about a qualitative research, that take on the narrative perspective as they resort to the oral history about the envolved subjects, contemplating significative aspects to their professional graduation that help to understand their habitual practice. This research shows despite legal support from 1988, the right of school Indian education specified and differentiated it isn t still assured. By the interviews and the visits to Escola da Aldeia Piaçagüera, I could see the existence of the demand that deserve and need effective and urgent solutions by the public power, because they constitute significative for the consecution of the politic pedagogy project of Indian schools. Besides, the Indian teacher condition as a carrier of the tradition of the group and at the same time as a representative of the knowlegment established puts paradoxes to the teaching profession preparation and behavior. These questions must be equationed by the Indian people s vision in a perspective of autonomy and respect to the diversity